New atom transfer radical polymerization initiator based on phenolphthalein for the synthesis of bis-allyloxy functionalized polystyrene macromonomers - Patil, Sachin S.; Menon, Shamal K.; Wadgaonkar, Prakash P. (Polymer International, 2015)
A new atom transfer radical polymerization (ATRP) initiator, namely 2-(1,1-bis(4-(allyloxy)phenyl)-3-oxoisoindolin-2-yl)ethyl 2-bromo-2-methylpropanoate, was synthesized starting from phenolphthalein, a commercially available and an inexpensive chemical. Well- defined bis-allyloxy functionalized polystyrene macromonomers (M-n,M-GPC 4800-11 700gmol(-1)) with controlled molecular weight and narrow molecular weight distribution (1.05-1.09) were synthesized using ATRP by varying the monomer to initiator feed ratio. The presence of allyloxy functionality on polystyrene was confirmed by Fourier transform infrared and H-1 NMR spectroscopy. A kinetic study of polymerization revealed pseudo-first-order kinetics with respect to monomer consumption. Initiator efficiency was found to be in the range 0.80-0.95. Matrix-assisted laser desorption ionization time of flight spectra showed a narrow molecular weight distribution with control over the molecular weight. The reactivity of the allyloxy groups on polystyrene was successfully demonstrated by quantitative photochemical thiol-ene click reaction with benzyl mercaptan as the model thiol reagent. Furthermore, the thiol-ene click reaction was exploited to introduce other reactive functional groups such as hydroxyl and carboxyl by reaction of ,-bis-allyloxy functionalized polystyrene with 2-mercaptoethanol and 3-mercaptopropionic acid, respectively. (c) 2014 Society of Chemical Industry
Keywords: atom transfer radical polymerization; bis-allyloxy functionalized polystyrene; functional initiator; phenolphthalein; thiol-ene click reaction